An Analysis of the Learning Activities Covered in the 5th Grade Science Textbooks Based on 2005 and 2013 Turkish Science Curricula - Cemil Aydogdu; Sahin Idin (Journal of Education in Science, Environment and Health)
The aim of this study is to analyze the learning activities covered in 5th grade elementary science textbooks which depend on 2005 and 2013 elementary science curricula. Two elementary science textbooks depends on 2005 science curriculum and two elementary science textbooks depend on 2013 science curriculum were researched. The study is a qualitative research and the data were analysed through the document analysis technique. The findings revealed that textbooks based on 2005 science curriculum includes more activities. In addition, these activities were found to be designed to evaluate student learning. There was no preparation for workbooks in 2013 science curriculum. Based on the findings obtained some suggestions are developed about the design of the textbooks.